Peningkatan Hasil Belajar Siswa Menggunakan Model Pembelajaran Problem Based Learning Didukung Media Smart Box Dan Kartu Domino Di SMP Negeri 1 Umalulu - Agustina Uru Bunggih; Anita Tamu Ina; Riwa Rambu Hada Enda (BEST Journal (Biology Education, Sains and Technology), 2025)
The purpose of this study is to improve student learning outcomes after using problem-based learning models assisted by smart box media and domino cards. The results of this study indicate that the application of problem-oriented learning methods, known as Problem Based Learning, combined with tools such as smart boxes and domino cards, can improve students' academic achievement, especially in the material on the earth and the solar system. The cause of this study is the low academic results of students caused by the selection of inappropriate methods. This study uses a classroom action method that is carried out in two cycles through four stages, namely: planning, implementation, observation, and reflection. The results of the study showed a significant increase in learning outcomes after the application of problem-based learning methods using smart box media and domino cards. In the cognitive aspect, in the pre-cycle, only 22.58% of students met the minimum completion standard, while in cycle I, the percentage increased to 38.30%, and in cycle II, the number of students who achieved completion jumped to 90.33%. In the affective aspect, in the pre-cycle, there were 16.12% of students who achieved completion, this figure increased to 70.97% in cycle I, and in cycle II increased again to 90.55%. Therefore, the results of this study indicate that the use of problem-focused learning models supported by smart box media and domino cards has proven effective in improving student learning outcomes, both in terms of cognitive and affective aspects.